THE PRACTICE OF BUDGET FINANCING OF EDUCATION EXPENSES IN UZBEKISTAN (E Conference Zone, 2023)
In our country, the issue of ensuring a thorough education of young people, their respect for national traditions and values is one of the priorities of state policy. The ultimate goals of building a free democratic civil society, achieving high economic development and ensuring the well-being of the population cannot be achieved without radically changing the education system and rebuilding it on a modern basis. It is important for the country what the state of the education system in the country is, especially the public education system, and what kind of personnel will be trained in the future.